Influencing factors of organic waste segregation in the generating source for feasibility of composting systems - Pereira, Vanessa Rodrigues [UNESP]; Fiore, Fabiana Alves [UNESP] (FapUNIFESP (SciELO), 2022)
Organic waste is a considerable fraction of urban solid waste generated worldwide. Composting is one type of treatment of this waste that has the advantage of requiring low investments and simplicity in operations. However, to guarantee efficiency in composting, the segregation in generation sites and the wide participation of the population are crucial. In this sense, understanding the separation behavior of the population and the performance of the governments is especially important to the continuity and improvement of these systems. In this context, the aim of this paper was to identify the factors that influence the behavior segregation of organic waste in the generating sites, for the purposes of treatment in composting systems. The systematic review was performed using the Archive Search Method. It was found that the factors influencing organic matter segregation are: physical infrastructure and convenience, education, sociodemographic data, economic factors, social norms and influence, feedback, habit, pro-environmental behavior, confidence in the system, and factors associated with the Theory of Planned Behavior. It was concluded that there is no consensus on the intensity and aspect (positive or negative) of the impact of the factors, as they depend on local particularities. Once there is an interdependent relationship, a set of factors must be considered to ensure adequate planning. In composting systems, the evaluation of separation efficiency can be carried out indirectly, centered on the individual’s perception and self-report of behavior; or directly, with gravimetric and composition measurement. to the adoption of both forms, in a complementary way, is recommended.
Fatores influenciadores da segregação de resíduos orgânicos na fonte geradora para a viabilização de sistemas de compostagem
Keywords: composting; influencing factors; organic waste; source separation